Manajemen Pendidikan Pesantren dalam Konteks Kebijakan Pendidikan Nasional: Analisis dan Rekomendasi - Rabiatul Adawiyah; Zahruddin Zahruddin; Maftuhah Maftuhah (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Pesantren as the oldest educational institution in Indonesia has a strategic role in shaping the character and morals of the nation. However, in the era of globalisation and technological advances, pesantren need to adapt to national education policies to remain relevant and effective. This article aims to analyse pesantren education management in the context of national education policy and provide recommendations for future development. The methods used are literature review and policy analysis. The results of the analysis show that pesantrens are distinctive in their education management, but require synergy with national policies to improve quality and competitiveness. Recommendations include strengthening the curriculum, improving the quality of teaching staff, and improving educational facilities and infrastructure.